Operant Conditioning Strategies in Limited Face-to-Face Learning Activities in Forming the Responsibility Character - Fitri Amelia Rosida; Ika Ari Pratiwi; Much Arsyad Fardani (Universitas Pendidikan Indonesia Kampus Serang, 2022)
The change in learning from what was originally face-to-face to distance learning and then switched to limited face-to-face learning made students need to adapt to all the provisions in the learning process. It then impacts the student's responsible character. This study, therefore, aims to discuss the process of forming the student responsibility character through the operant conditioning type in limited face-to-face learning activities. The research method used was qualitative with a narrative approach model. This study’s subjects were the principal, a fifth-grade homeroom teacher, and nine fifth-grade students of State Elementary School of 1 Barongan. Besides, data collection techniques employed were interviews, observation, and documentation. The data validity was tested by triangulation of sources and data collection techniques in the study. Data analysis techniques utilized were data reduction, data presentation, and conclusions. This study’s results highlighted those changes in the learning system impacted the student responsibility character; thus, there is a need for the formation of the responsibility character. The formation of the responsibility character will be more substantial if given direct reinforcement (Operant Conditioning Theory). Operant conditioning consists of two main concepts: reinforcement and punishment. Reinforcement is divided into positive reinforcement (such as attention, approval, and appreciation) and negative reinforcement (e.g., reducing material and giving assignment pause). Meanwhile, punishments encompass reprimands, emphasis, and additional assignments.